Izobraževanje o naravnih nesrečah v Evropi - Ciglič, Rok (Georitem, 2011)
This volume presents the importance of natural-disaster education for social preparedness. Increasing damage caused by natural disasters around the globe draws attention to the fact that even developed societies must adapt to natural processes. Natural-disaster education is a component part of any education strategy for a sustainably oriented society.